Artificial facilitation: Promoting collective reasoning within asynchronous discussions. Issue 3 (3rd July 2017) - Wyss, Dominik; Beste, Simon
ABSTRACT: Online forums have become prominent in deliberative research as venues for infusing democracies with additional participatory elements. However, forums are criticized as being unsuitable for high-quality discussions as they predominantly induce self-expressive talk with little prospect for deliberative virtues. Drawing on the "argumentative theory of reasoning, " we hypothesize that an artificial facilitator (AF) ameliorates deliberative virtues by spurring interactions among the users and promoting knowledge gain. In a randomized field experiment, we show that the AF indeed enhances interaction, but only partially increases knowledge gain. Psychological variables mediate whether participants learn more in a facilitated online forum.